An Investigation into the Potential Adoption of International Financial Reporting Standards in the United States: Implications and Implementation. Issue 1 (March 2016) - Tan, Aldys; Chatterjee, Bikram; Wise, Victoria; Hossain, Mahmud
Abstract : International Financial Reporting Standards (IFRS) have been adopted by most of the G20 countries. Given the broad worldwide acceptance of IFRS and significance of attaining comparability to facilitate free flow of capital, the US standard setter, the Financial Accounting Standards Board (FASB) made a commitment to jointly work with the International Accounting Standards Board (IASB) to explore the possibilities of convergence of US Generally Accepted Accounting Principles (GAAP) with IFRS. In 2007, the US Securities and Exchange Commission (SEC) eliminated the requirement that foreign companies listed on the US stock exchanges reconcile their IFRS‐based financial statements with the US GAAP. In the same year the US SEC issued a concept release to the public requesting comments on a proposal to allow US issuers to prepare financial statements in accordance with IFRS. Following these initiatives by the FASB and SEC, the aim of the present study is to investigate the implications of a potential full adoption of IFRS by the US. The present study details the challenges and benefits of adoption and outlines the steps required for a successful outcome of this process.